2017
DOI: 10.2151/jmsj.2017-002
|View full text |Cite
|
Sign up to set email alerts
|

The Asian Monsoon and its Future Change in Climate Models: A Review

Abstract: This study provides an overview of the Asian monsoon and its change as simulated by atmosphere-ocean coupled general circulation models and high-resolution atmospheric general circulation models, focusing on the seasonal mean circulation and precipitation climatology. After reviewing the drivers of and the elements that affect the monsoon, the ability of those climate models to reproduce the Asian monsoon is assessed. The Asian monsoon is better reproduced in the Coupled Modeling Intercomparison Project phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 210 publications
(260 reference statements)
7
50
0
Order By: Relevance
“…These simulations also project a rainfall increase related to the southeast Asian winter monsoon in response to cyclonic wind anomalies over the south China Sea (Siew et al, ). Although evident in some of the analyses dedicated to East Asian winter monsoon projections (e.g., Figure 7 from Ogata et al, and Figure 8 from Kitoh, ), this study is the first to discuss the projected decrease of the IWM circulation over the AS and the driving mechanisms. While both summer and winter Indian monsoonal circulation slowdown in CMIP models have been tracked back to changes in meridional temperature gradients between the IO and the northern IO landmass, the key continental regions involved differ substantially, with the summer monsoon involving temperature changes over the Tibetan Plateau (e.g., Sooraj et al, ) and winter monsoon being mainly influenced by temperature and SLP changes over the Arabian Peninsula and the Thar dessert.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…These simulations also project a rainfall increase related to the southeast Asian winter monsoon in response to cyclonic wind anomalies over the south China Sea (Siew et al, ). Although evident in some of the analyses dedicated to East Asian winter monsoon projections (e.g., Figure 7 from Ogata et al, and Figure 8 from Kitoh, ), this study is the first to discuss the projected decrease of the IWM circulation over the AS and the driving mechanisms. While both summer and winter Indian monsoonal circulation slowdown in CMIP models have been tracked back to changes in meridional temperature gradients between the IO and the northern IO landmass, the key continental regions involved differ substantially, with the summer monsoon involving temperature changes over the Tibetan Plateau (e.g., Sooraj et al, ) and winter monsoon being mainly influenced by temperature and SLP changes over the Arabian Peninsula and the Thar dessert.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…In the future, there was an overall tendency for wetter conditions over the northern‐central‐eastern part of Thailand and drier conditions in the southern region in the dry season, and drier conditions over the entire country in the wet season (Figures ). It can be generally deduced in Figure that despite intra‐seasonal differences within a particular season, both the winter and summer regional circulations are projected to weaken, consistent with previous studies (e.g., Siew et al ., ; Kitoh, ). During dry months, it can be seen that the easterly/northeasterly winds over Indochina weaken.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of researches have shown that global warming will increase the overall precipitation associated with the East Asian summer monsoon including the East Asian Meiyu (Kitoh, 2017), but no consensus has been reached on its spatial distribution in CMIP5 models (Liang et al, 2016; Wu et al, 2019). Horinouchi et al (2009) suggested that the Baiu rainband shift southward by the late 21st century, and Meiyu location is unidentified.…”
Section: Meiyu Modelling and Predictionmentioning
confidence: 99%